Aged kidney: can we protect it? Autophagy, mitochondria and mechanisms of ischemic preconditioning. Issue 11 (3rd June 2018) - Jankauskas, Stanislovas S.; Silachev, Denis N.; Andrianova, Nadezda V.; Pevzner, Irina B.; Zorova, Ljubava D.; Popkov, Vasily A.; Plotnikov, Egor Y.; Zorov, Dmitry B.
ABSTRACT: The anti-aging strategy is one of the main challenges of the modern biomedical science. The term "aging" covers organisms, cells, cellular organelles and their constituents. In general term, aging system admits the existence of nonfunctional structures which by some reasons have not been removed by a clearing system, e.g., through autophagy/mitophagy marking and destroying unwanted cells or mitochondria. This directly relates to the old kidney which normal functioning is critical for the viability of the organism. One of the main problems in biomedical studies is that in their majority, young organisms serve as a standard with further extrapolation on the aged system. However, some protective systems, which demonstrate their efficiency in young systems, lose their beneficial effect in aged organisms. It is true for ischemic preconditioning of the kidney, which is almost useless for an old kidney. The pharmacological intervention could correct the defects of the senile system provided that the complete understanding of all elements involved in aging will be achieved. We discuss critical elements which determine the difference between young and old phenotypes and give directions to prevent or cure lesions occurring in aged organs including kidney. Abbreviations: AKI: acute kidney injury; I/R: ischemia/reperfusion; CR: caloric restriction; ROS: reactive oxygen species; RC: respiratory chain